TCF7L2 promotes ER stress signaling in diabetic retinopathy. (August 2022) - Wu, Keling; Zhou, Kesi; Zhao, Minglei; Xiang, Lijun; Mei, Tingfang; Xu, Wenchang; Shang, Bizhi; Liu, Xinqi; Lai, Yuhua; Lin, Mingkai; Luo, Jingyi; Zhao, Ling
Abstract: Diabetic retinopathy (DR) is one of the most common blindness in working-age adults. Transcription factor 7 like 2 ( TCF7L2 ) is a susceptibility gene of DR, however, its roles in the pathogenesis of DR are still largely unknown. In this study, we found that TCF7L2 was mainly located in the cell nucleus of retinal ganglion cell layer (GCL) and inner nuclear layer (INL), while it was not expressed in the cell nucleus of retinal outer nuclear layer (ONL). Expression of TCF7L2 was significantly elevated in the retinas of db/db diabetic mice and oxygen-induced retinopathy (OIR) mice. Also, in Ad-hTCF7L2 treated hiPSCs-derived retinal progenitor cells (RPCs), activating transcription factor 6 (ATF6)-related endoplasmic reticulum (ER) stress signaling was remarkably activated. Moreover, knockdown of TCF7L2 significantly inhibited ATF6-related ER stress signaling. Furthermore, the data of endothelial permeability assay showed that RPCs pretreated with Ad-hTCF7L2 lead to enhanced monolayer permeability of human umbilical vein endothelial cells (HUVECs), and knockdown of TCF7L2 or ATF6 in RPCs could alleviate the monolayer permeability of HUVECs. Thus, our results showed that TCF7L2 could trigger ATF6-related ER stress signaling and promote vein endothelial cell permeability, which will provide important insight into the role of TCF7L2 in the pathogenesis of DR and contribute to designing potential therapies. Highlights: TCF7L2 is mainly located in retinal neural layers. TCF7L2 is a crucial trigger in promoting ATF6-related ER stress signaling. Elevated TCF7L2-ATF6 signaling is involved in neurovascular pathogenesis of diabetic retinopathy.